SORTING HILLS CURRENT PROBLEMS IN AUTOMATION AND TELEMECHANICS SYSTEMS - Toshboyev Zokhid Bakhron o‘gli; Khamdamova Lola Olimjon kizi; Mustafayeva Kamola Nuriddin kizi (International Journal of Innovations in Engineering Research and Technology, 2022)
In this article, the existing problems encountered in railway sorting peaks automation and telemechanics systems are considered. It focuses on solutions to the problems of disconnecting disconnections from the peak as well as connecting and slowing down the content. The way of connecting the automation and telemechanics control devices on the railway sorting Hills with the electric centralization system is illuminated.